English FRACTAL ANALYSIS OF THE FLOUR - Kubik, Lubomir (Journal on Processing and Energy in Agriculture, 2020)
ABSTRACT The aim of the manuscript was the evaluation of the microscopic, powder samples of the flour by means of the fractal analysis. The powder particles were compared and submitted of the fractal analysis. The three flours were studied, the smooth flour, semi-flour and thick flour. The five samples of the each sort of the flour were tested by the fractal analysis. The samples were digitized by the digital microscope Motic DM 1802-A with software Motic Image Plus ver. 2.0. Each image was processed by the thresholding operation and the fractal analysis was realized by the software Harfa ver. 5.1.0 and the samples were compared by the correlation analysis. The obtained fractal dimensions described the segmentation and distribution of flour powder and the fractions of the flour. The fractal dimension of the smooth flour was DWBW = 1.29266, of the semi-flour DWBW = 1.70734 and of the thick flour DWBW = 1.57978. The smooth flour was composed from the microscopic powder particles of the wheat. Mainly small particles about 10 μm were included in the smooth flour but also the sporadic particles greater than 47.6 μm were observed. The size of the smooth flour particles was from 2.38 μm to 47.6 μm. Semi-flour contented mainly the particles of the size to 71.2 μm. The semi-flour obtained practically half particles of the size to 71.2 μm. The thick flour was created mainly by the particles to the size 73.78 μm. The greater particles of the size from 130.9 μm to 314.2 μm were obtained in the small number. On the base of the particles distributions were the semi-flour and thick flour very similar, but on the base of fractal analysis were different and we can distinguish them. Key words: powder, flour, fractal